Primeiro isolamento de Erysipelotrix sp. strain 2 em perus com septicemia no Brasil: Epidemiologia e Morfometria celular - Reis, Thais Fernanda Martins Dos (2019)
The genus Erysipelothrix compises by six species: E. rhusiopathiae, E. tonsilarium, E. inopinata, Erysipelotrix sp. strain 1, Erysipelotrix sp. strain 2 and Erysipelotrix larvae sp. Among then, E. rhusiopathiae is cosmopolitan and the main agent which causes the Erysipelas in poultry, swine and human. However, this study shows the association of an outbreak in turkeys with another very little reported species Erysipelotrix sp. strain 2. The data used to perform this work came from samples of commercial and breeder turkeys from a large company in the state of Minas Gerais, Brazil. First, as described in article 1, samples of turkeys’ organs (liver, spleen, lungs, trachea, kidneys, intestine and joints) from 118 farms associated to the company were submitted to bacteriological analysis for Erysipelothrix spp. and other bacterial diseases that cause similar clinical signs. Macroscopic lesions revealed a generalized septicemia, the animals presented weakness and high mortality. Real-time PCR identified as positive for Erysipelotrix sp. strain 2 in 15.5% of the samples. From these positive samples, 6 (six) isolates were sent for the 16S rRNA region sequencing. We identified high similarity with E. tonsillarum and E. rhusiopathiae. Antimicrobial susceptibility testing showed high resistance to neomycin, apramicyn, fosfomycin and sulfametoxazol / trimethoprim and intermediate resistance to tetracycline and sensitivity to norfloxacin, amoxicillin, lincomycin / spectinomycin. In the second chapter, we investigaled another outbreak. We evaluated a total of 92 samples from 31 flocks and from these, 30 samples were derived from 8 flocks where turkeys had sepsis and high mortality. All 30 samples from the positive flocks were positive for Erysipelotrix sp. strain 2 and we have not found any other species of Erysipelothrix spp. Transmission electron microscopy presented the structures of Erysipelotrix sp. strain 2, which in a longitudinal section had a rod format, and in a cross section, circular structure, and we also observed the plasma membrane and bacterial wall. For epidemiological data evaluation, the correlation analysis was positive for the parameters of final mortality, animals’ age during the outbreak and proximity to commercial swine system production (up to 7 km). The performance of PFGE in 19 samples for genotyping elucidated the presence of 2 clones from the same farms but from different turkeys and 2 clusters. However, we highlight the high genetic variability of the studied strains. To visualize the cellular alteration, we inoculated two Erysipelotrix sp. strain 2 isolates in Vero cell culture for evaluation of cell morphometry. Therefore, we can observe that the bacterium was able to increase the cell, nucleus and nucleolus area and perimeter. This study is very important, because it reveals the specie Erysipelotrix sp. strain 2 as the causative agent of Erysipelas in turkeys and for the first time shows characteristics of Erysipelotrix sp. strain 2 not published in the literature so far.